2020
DOI: 10.1111/imcb.12406
|View full text |Cite
|
Sign up to set email alerts
|

ROR agonist hampers the proliferation and survival of postactivated CD8+ T cells through the downregulation of cholesterol synthesis‐related genes

Abstract: Cholesterol is a major component of the lipid bilayers of cellular membranes. The synthesis of cholesterol is acutely elevated during T‐cell activation to support T‐cell growth and proliferation. There is a limited understanding of cholesterol metabolism reprogramming during T‐cell activation. Retinoic acid receptor‐related orphan receptors (RORs) are ligand‐activated nuclear receptors that regulate the transcription of target genes. In this study, we demonstrated that the activation of RORs by a synthetic ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Loss of RORα results in progressive, diverse testicular damage and leads to apoptosis, suggesting that RORα knockout promotes apoptosis in the testicle [35]. However, other studies revealed the proapoptosis effect of RORα in different cell types [36,37], suggesting the complexity of RORα in regulating cell senescence and apoptosis. Mediators of Inflammation TNF-α is regarded as one of the most critical factors contributing to IDD's pathogenesis [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of RORα results in progressive, diverse testicular damage and leads to apoptosis, suggesting that RORα knockout promotes apoptosis in the testicle [35]. However, other studies revealed the proapoptosis effect of RORα in different cell types [36,37], suggesting the complexity of RORα in regulating cell senescence and apoptosis. Mediators of Inflammation TNF-α is regarded as one of the most critical factors contributing to IDD's pathogenesis [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the augmentation of cholesterol generation is a hallmark of lipid metabolism during T cell activation and functions, by supporting the synthesis of cellular and organelle membrane ( 13 , 55 ). Retinoic acid receptor-related orphan receptors (RORs)-induced downregulation of cholesterol-metabolizing enzymes dramatically inhibits the proliferation and survival of CD8 + T cells ( 56 ). In addition, inhibition of acetyl‐CoA acetyltransferase (Acat) 1 and 2, enzymes involving in cholesterol esterification and storage, can further promote the proliferation and functions of CD8+ T cells by increasing cholesterol levels ( 57 ).…”
Section: The Role Of Metabolic Reprogramming In T Cell Activation And...mentioning
confidence: 99%
“…Cholesterol maintains quiescence in naïve T cells and also paradoxically regulates exit from quiescence by modulating TCR nanocluster formation besides effecting signaling molecules (18)(19)(20). T cell activation induces an increase of intracellular cholesterol for proliferation, however self-regulation is secured by negative feedback pathways (21)(22)(23)(24). Moreover, cholesterol is also involved in the differentiation and stabilization of the different T cell subsets.…”
Section: Introductionmentioning
confidence: 99%